Induksi Kalus pada Kultur Pollen Phalaenopsis dengan Menggunakan Asam 2,4-Diklorofenoksiasetat - NI PUTU MERTHANINGSIH; HESTIN YUSWANTI (Fakultas Pertanian Universitas Udayana, 2018)
Callus Induction on Phalaenopsis Pollen using 2,4-Dichlorophenoxyasetic acid. Tissue culture is one of the modern methods of plant propagation. In tissue culture hormone has an important role. The goals of this research was to determine the effect of 2,4-D hormone on callus growth of Phalaenopsis pollen explants on NP media and to know the most optimal concentration for the formation and growth of explants. This research used the complete randomized design with five treatment of 2,4-D dosage such as 0 ppm, 0.5 ppm, 1 ppm, 1.5 ppm, and 2 ppm. The variables observed in this research was time of explant swollen, percentage of explant swollen, time of explants detached, percentage of explants detached, time of callus growing, percentage of explants grow callus, callus colour, and callus texture. The result of analysis was 1,5 ppm of 2,4-D treatment gave the best effect to explants, with the fastest swollen explants time of 3 days after culture, the highest swollen explants (86.6%), the fastest detached explants (7.4 days after culture), and the highest detached percentage (66.6%), time of explant growth callus (28.4 days after culture) and percentage of explant growth callus (53.3%).